Lateral Thinking Ability Analysis in Preparation of Science Teacher Candidate Papers and Reports - Vica Dian Aprelia Resti; Aditya Rakhmawan (Bioeducation Journal, 2021)
The preparation of papers and reports is also an alternative solution to the problem of low reading and writing skills among students. The improvement of reading and writing skills is integrated in the preparation of papers and reports through a lateral thinking style in finding problem-solving solutions. This study used a quantitative descriptive approach to describe the lateral thinking skills of second semester science teacher candidate students in the preparation of papers and reports conducted during twelve meetings. The study population involved a total of 36 students of the Department of Natural Science Education, Campus III FKIP Sultan Ageng Tirtayasa University, Jalan Ciwaru Raya, Serang, Banten. Some of the aspects contained in the assessment rubric are the systematics of papers and reports, the flow of thought and the casting of ideas. The number of students who managed to get the highest score at the meeting before UTS was 18 students, 6 students scored 88, 6 students scored 84 and 6 students scored 82. These results differ from the number of students who managed to get the highest score at the meeting after the UTS, namely 6 students, 6 students scored 86, 18 students scored 84 and 6 students scored 82. The existence of differences in results at the meeting before and after the implementation of the UTS is an indication that presenting learning activities that provide experiences to students involves the role of several aspects. Some of these aspects include the scope of the problem, the choice of learning methods and the learning experiences of previous students.